The practice of adaptive leadership tools and tactics for changing your organization and the world - Heifetz, Ronald A. (Boston Harvard Business Press, 2009)
When change requires you to challenge people's familiar reality, it can be difficult, dangerous work. Whatever the context--whether in the private or the public sector--many will feel threatened as you push though major changes. But as a leader, you need to find a way to make it work.
Includes bibliographical references (p. [299]-301) and index.
Keywords: Leadership